Charity and Commercial Success as Vectors of Asymmetry and Inequality: The Unconceptualised Elements of Development in Islamist Sudan during the First Republic - Raphaëlle Chevrillon-Guibert (Revue Internationale de Politique de Développement)
The Sudanese Islamist experiment is far from having put an end to the conflict-ridden history of the country, despite the South achieving independence in July 2011. However, a higher degree of regional integration outside the South was one of the stated aims of the Islamists when they came to power in 1989. This chapter will investigate the apparent paradox by exploring the experiments in development undertaken by Sudanese Islamists during their first republic (1989-2011) on the basis of the study of certain social practices they actively encouraged, namely evergetism and philanthropy. It is based on an analysis of the charitable practices carried out by the main traders in the Sudanese capital’s principal market during the Islamist regime. The regional –more specifically Darfurian– origin of most of these main traders makes it possible to compare what these practices produce in each different territory. The chapter shows that this encouragement, which is not part of any specific plan thought up by the Islamists, leads to different forms of development that vary depending on the local and human contexts in which the actors live, and also the way they conceive their roles within the circles to which they belong. It then highlights how these variations produce extremely disparate and often conflict-ridden results, which ultimately pursue the asymmetric formation of the Sudanese state, prolonging a historical trajectory that has produced injustice and generated conflict (Figure 11.1).